Pengendalian kualitas produk pada Konveksi Deanisa Sport untuk meminimasi defect dengan menggunakan metode Six Sigma - Napu, Kartika; Wolok, Eduart; Lahay, Idham Halid (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Convection Deanisa Sport is a business that moves in the production of clothing, among other office uniforms, school uniforms, alma mater jackets, and training sets. This convection is located on Jl. Jaksa Agung Suprapto No.5, Limba U Dua, Kota Selatan, Kota Gorontalo. From the results of initial observations in the field, defective products resulting from convection are still quite a lot in the period from 2023 to 2024. Some products that experience defects include errors in cutting, and the sewing process. the average percentage of defects by 10%. Of course, this percentage is very high for the scale of MSME convection Deanisa, so that for the limitation of product defect tolerance used, it is 2.5% - 3% by referring to research reports (Pratomo & Prassetiyo, 2023) and Research reports (Suhadak & Sukmono, 2021) that conduct research in MSMEs with the same scale as convection Deanisa. Therefore, in this research the author will analyze the quality of products using the six Sigma method through DMAIC steps in the convection process to identify product defects and evaluate the production process in creating products that are in accordance with the specified standards.